Penggunaan Fitur Laporkan dalam Twitter Sebagai Upaya Literasi Digital Guna Ketahanan Nasional - Navara Darisya Salma (Public Inspiration : Jurnal Administrasi Publik, 2022)
In the implementation of national resilience, there are many ways to do it. Digital literacy is the solution and goal of implementing certain elements in national security. Focusing on research on the effectiveness of existing features on Twitter social media. The results of this study are used as an answer to the form of successful interpretation of digital literacy. The topic of this discussion is expected to provide knowledge about the importance of mastering digital literacy as a guide for social media and emphasizes that the form of implementing national resilience can vary. This research was carried out with quantitative and qualitative methods. Using primary and secondary data in the research process. The distribution of the questionnaire survey is a form of the use of quantitative methods that recruit respondents according to the conditions given. The secondary data used are literacy studies from books, articles, websites, and indirect observations as a form of qualitative method. The results of this study used a qualitative descriptive approach in accordance with the findings of supporting data in the study. Thus, national resilience can be maintained because the practice of digital literacy can be carried out well among the Indonesian people. After that, peace between individuals and the people can be realized properly.